Penerapan Metode Resitasi Untuk Meningkatkan Hasil Belajar Kelas IV Muatan IPS 7 UPTD SDN Banyuajuh 5 - Depi Ratnasari; Sri Wahyuning Tiyas; Putri Nihayatut Thoyibah; Agung Setyawan (Lembaga Pengembangan Kinerja Dosen, 2023)
This research was motivated by the low learning outcomes of class IV UPTD SDN Banyuajuh 5 students in Social Science content. The purpose of this study was to determine the effect of applying the recitation method on student learning outcomes. The type of data in this study is quantitative data, namely data on the results of student work obtained from the initial test and the final test of the actions of each cycle. This study uses a class action research approach (CAR) with the implementation cycle of cycle I and cycle II. The results of the study concluded that the completeness of student learning outcomes before the action only reached 2 students (9.09%) complete, while 20 students (90.91%) did not complete. Then after the action cycle I experienced an increase to 6 students (31.82%) completed and 16 students (68.18%) did not complete. In the action in cycle II, student completeness exceeded 80%, namely with 81.82% completeness with 18 students reaching the KKM that had been set, namely 73.